Healthy Eating for Elders: Nutrition and Diabetes - Jennifer Hillan (EDIS)
A healthy diet, along with exercise and medication, can help control diabetes and reduce the risks for diabetes complications. It will also help people at high risk for diabetes reduce the chance of getting the disease. This leaflet contains some tips for a healthy diet. This document, FCS8612-Eng, is one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.